2016
DOI: 10.1021/acsami.6b07412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Premetallization Surface Preparation on Nickel-based Ohmic Contacts to Germanium Telluride: An X-ray Photoelectron Spectroscopic Study

Abstract: Surfaces of polycrystalline α-GeTe films were studied by X-ray photoelectron spectroscopy (XPS) after different treatments in an effort to understand the effect of premetallization surface treatments on the resistance of Ni-based contacts to GeTe. UV-O is often used to remove organic contaminants after lithography and prior to metallization; therefore, UV-O treatment was used first for 10 min prior to ex situ treatments, which led to oxidation of both Ge and Te to GeO (x < 2) and TeO, respectively. Then the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…The binding energies of the four peaks coincide with literature values for GeTe. [22][23][24][25]28,29 The binding energies in amorphous and crystalline GeTe are very close 28,29 but from the STEM studies presented above, one can safely conclude that the XPS spectra of Figures 4g−j were measured in the amorphous part of the film, below the limit of the oxygen penetration.…”
Section: ■ Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The binding energies of the four peaks coincide with literature values for GeTe. [22][23][24][25]28,29 The binding energies in amorphous and crystalline GeTe are very close 28,29 but from the STEM studies presented above, one can safely conclude that the XPS spectra of Figures 4g−j were measured in the amorphous part of the film, below the limit of the oxygen penetration.…”
Section: ■ Resultsmentioning
confidence: 93%
“…To explore the nature of chemical environments in the surface-oxidized GeTe film, we performed XPS depth profiling at room temperature (Figure ). We measured the Te 4d and Ge 3d spectra and the Te 3d 3/2 and Te 3d 5/2 spectra, which are relevant for studying GeTe oxidation. …”
Section: Resultsmentioning
confidence: 99%
“…Bates et al have shown that SnTe is stable against the reaction with Fe. Because the HCl treatment leaves the surface Te-rich, the subsequent SnTe layer formed is thicker in the HCl-treated sample than in the DI H 2 O-treated sample (Ge-rich surface). The thicker SnTe may act as a barrier to the formation of a Fe–Ge layer above SnTe and reduce the diffusion of Fe into GeTe.…”
Section: Results and Discussionmentioning
confidence: 96%
“…We have recently shown that both DI H 2 O and HCl treatments are effective in removing surface oxides GeO 2 and TeO 2 , though they do not passivate the surface. Ge-rich and Te-rich surfaces are obtained by DI H 2 O and HCl treatments, respectively . Therefore, a greater amount of SnTe or Ge x Sn 1– x Te alloy at the interface might form after the HCl treatment.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation